Physiological and metabolic factors determining nitrogen use efficiency of tomato seedlings grown with elevated dissolved inorganic carbon and different nitrogen sources - Viktor, Aleysia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2002.